(untitled) (translation. a transdisciplinary journal, 2021)
translation editor Siri Nergaard met with translation studies pioneer Susan Bassnett in Bologna (Italy) on one of che scholar’s frequent travels to the country where she studied and starred her career as a scholar of comparative literature. During this conversation Bassnerc cells about her life in and around translation, speaks of the origins of her many publications (including the ground-breaking Translation Studies, fi.rsc published in 1980 and now going into its 4th edition), and reflects on the close professional friendships from around the world chat she has forged in pursuit of her cransdisciplinary studies. Together, the scholar and editor explore the very nature of translation and speculate about where study of translation is heading. ’Change comes from che margins’. Bassnecc reminds us. Bassnetc has implemented and witnessed many changes in her long. diverse, and still thriving career. Her history is in many ways che history of translation studies. The following is a transcript of the oral interview.